Semantical Interpretations of the Temporal Logic Systems CL and Kb with the Gaps of Traditional Truth-values - Pabijutaitė, Živilė (Problemos, 2020)
Over the past several decades, in the field of temporal logic there have been created a great number of semantical theories that provide different truth conditions for tensed propositions. In this article we deal with five non-bivalent semantical interpretations of the temporal logic systems CL (Cocchiarella Linear) and Kb (Kripke Branching): 1) Ł3 by J. Łukasiewicz; 2) K3 by S. C. Kleene; 3) Ockhamism by A. Prior; 4) supervaluationism by R. Thomason; 5) relativism by J. MacFarlane. The aim of this article is to present a detailed typology of the five semantical theories based on these criteria: a) the ability to deal with the problem of retrospective evaluation of future contingent propositions; b) the ability to deal with the problem of divine omniscience and free will; c) their relation to the law of excluded middle; d) their relation to other formulas that are intuitively acceptable in an intederministic context. It is argued that the only theory that satisfies all four criteria is the relativism of J. MacFarlane; however, it faces some serious challenges when dealing with the problem of retrospective evaluation of future contingent propositions in the theological context.
Keywords: future contingents; determinism; temporal logic; bivalence